Preliminary manufacturability evaluation of complex geometrical parts based on layer thickness in the metal powder bed fusion process - Deep, Akash; Piili, Heidi; Miri Beidokhti, Mojtaba (Springer, 2025)
Powder bed fusion of metals using a laser beam (PBF-LB/M) is a widely adopted additive manufacturing (AM) technique, particularly effective for producing complex geometries and thin-walled structures. While thin powder layers enable high precision and fine surface finishes, they also reduce manufacturing speed, creating a trade-off between quality and productivity. This study explores the relationship between geometrical complexity and manufacturability in PBF-LB/M by developing a specialized numerical framework. A comprehensive review of existing manufacturability evaluation methods, which focusses on feature-based and knowledge-based approaches is presented, with applications across the aerospace, biomedical, and automotive industries. The study highlights the importance of layer thickness as a key process parameter and conducts a preliminary evaluation of its impact on building time and manufacturability. The proposed framework provides step-by-step guidance to support early-stage design decisions, allowing optimization of part geometry for reduced cycle time and cost. Initial validation is performed using industrial case studies and build-time simulations using Aconity and Netfabb software. Although the current focus is on layer thickness, the framework sets the groundwork for future studies that incorporate broader process parameters, contributing to improved manufacturability evaluation and decision-making in AM.